2012
DOI: 10.5194/angeo-30-515-2012
|View full text |Cite
|
Sign up to set email alerts
|

Magnetopause energy transfer dependence on the interplanetary magnetic field and the Earth's magnetic dipole axis orientation

Abstract: Abstract. We examine the spatial variation of magnetospheric energy transfer using a global magnetohydrodynamic (MHD) simulation (GUMICS-4) and a large data set of flux transfer events (FTEs) observed by the Cluster spacecraft. Our main purpose is to investigate whether it is possible to validate previous results on the spatial energy transfer variation from the GUMICS-4 simulation using the statistical occurrence of FTEs, which are manifestations of magnetospheric energy transfer. Previous simulation results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Variations in the cross-polar cap potential thus seem to be largely (70-90%) due to variations in solar wind-magnetosphere coupling. A recent study by Palmroth et al [2012] also demonstrated that there is a seasonal difference in this coupling. Their simulations showed a $10% larger energy transfer from the solar wind to the magnetosphere at equinox compared to solstice.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Variations in the cross-polar cap potential thus seem to be largely (70-90%) due to variations in solar wind-magnetosphere coupling. A recent study by Palmroth et al [2012] also demonstrated that there is a seasonal difference in this coupling. Their simulations showed a $10% larger energy transfer from the solar wind to the magnetosphere at equinox compared to solstice.…”
Section: Discussionmentioning
confidence: 82%
“…While this difference is smaller than what we report here, it agrees qualitatively with our results. Palmroth et al [2012] also noted that the energy transfer at solstice takes place preferably in the summer hemisphere. This is again consistent with our results, as we find that the separator line is tilted within the GSM x-z plane, such that the subsolar point on the separator line is in the summer hemisphere, and its tailward end in the winter hemisphere, although this is difficult to see in Figure 4.…”
Section: Discussionmentioning
confidence: 94%
“…If, for some reason, the reconnection site regularly formed significantly northward of the magnetosheath stagnation point in the Northern Hemisphere winter, and southward of the stagnation point in the Southern Hemisphere winter, then the single X line reconnection process could give rise to a seasonal bias in the same sense as the Raeder [2006] model predicts, and was observed by Korotova et al [2008] and in this study. Possible north–south asymmetries in the location of the reconnection line are still under investigation [ Palmroth et al , 2012], but unless a mechanism is found that consistently moves a single X line toward the winter hemisphere then we suggest that the observed seasonal bias is more likely to be caused by sequential multiple X line reconnection as modeled by Raeder [2006].…”
Section: Discussionmentioning
confidence: 92%
“…Presentation of these magnetopause crossings on a single magnetopause surface is problematic because the wide range of IMF and solar wind conditions indicate different sizes of the magnetopause surface. Furthermore, the Earth's dipole tilt angle has an effect on the location of the load and generator [ Palmroth et al ., ]. Hence, energy conversion during a crossing may indicate a load, but the location of a crossing may fall within a generator region if the dipole tilt angle is not taken into account.…”
Section: Data Setmentioning
confidence: 99%